Health and usage monitoring system for military vehicles - Al Abri, M. S. (Cranfield University, 2019)
The aircraft industry has been able to adopt improved maintenance and logistics planning as a result of the technological advances in Integrated Modular Avionics (IMA) and Equipment Health Monitoring (EHM). Same cannot be said about the land system. In the land environment, military vehicles are well behind in achieving the same abilities and hence, the problem of inefficiency in the maintenance and logistics for land based system needs to be addressed. To address this and assess the viability of integrating HUMS and Autonomic Logistics on military land vehicles, this project was proposed. Three main contributions from this research which adds to the knowledge are: (1) assessment of some real system failure which could lead to a poor operational readiness, (2) evaluation of how HUMS can improve the availability and operational readiness and reduction in maintenance cost that leads to the development of cost model and (3) a use of case studies to evaluate degradation of systems under consideration and how their continuous monitoring can help reduce the maintenance cost. A cost modelling study presented a simple and effective method to analyse the financial implication of integrating HUMS system was proposed for military land vehicles. The model provides logical steps to estimate the yearly repair costs, operational availability and the overall costs to understand the financial implication of HUMS integration over the whole service life. The model was also used to assess the financial viability of integrating HUMS in other military platforms e.g. light armoured vehicle, Piranha and Main Battle Tank, Challenger 2. In both the cases, the analysis showed significant financial savings in the long term. A case study was conducted on two different military vehicles to identify the frequency of different systems and sub-systems failures. The 20 challenger 2 and 40 Piranha were studied over the period of 10 years of service time. Study has found that cooling-, lubrication- and the suspension- system were the mostly affected systems in those particular vehicles. An experimental protocol was developed to study the failure detection techniques for the suspension system. The frequency response function was used to identify the failure of the damper and hence the suspension system. The study has observed the changes in the resonance frequency of the failed suspension system with different excitation magnitudes. Effect of vibration waveform was observed to be negligible. However, the small changes in the resonance frequencies using different magnitudes of base excitation seems to suggest the excitation magnitude has the potential to identify the failure based on the frequency response function.Another experimental protocol was developed to examine the failure detection technique for the cooling system of the military vehicle. When the failure was introduced to the cooling system, the significant variations in the temperature were observed for all the engine running conditions at the lab as well as the test with the vehicle running in the field. The variations observed in the temperature measured in different locations in the cooling system could be used to diagnose an early stage of failure in the cooling system, and it can be used to take a preventive action before the actual failure occurs.
© Cranfield University, 2019
Keywords: Dampers; Health and usage monitoring (HUMS); Suspension; Failure; Cooling systems; Condition based maintenance (CBM); Airborne laser scanning (ALS); Temperature